Effect of Multi-Enzyme Supplementation on Growth Performance of Rabbits - Mohammed, Alhassan (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2023)
The aim of this study is to determine the effect of enzyme supplementation in diets of rabbits on their growth performance, carcass and organ characteristics as well as haematological profile of rabbits. The rabbits were fed commercial diets containing 15% crude protein and metabolizable energy of 2650 kcal. The treatment diets were formulated by adding the enzyme (Kemzyme Plus) to the diets at 0mg/kg, 250mg/kg, 500mg/kg and 1000mg/kg respectively. Twenty (20) weaner rabbits were divided into four groups of five rabbit per group. Each group represent a treatment with 5 replications in a Complete Randomized Design (CRD). The results of growth performance indicated that rabbits fed diets containing 1000mg/kg of Kemzyme had a significant higher (P<0.05) feed intake than those rabbits fed 250 and 500mg/kg of the Kemzyme, which had a comparable feed intake but higher (P<0.05) than those rabbits fed the control diet. The control group had the lowest (P<0.05) weight gain and those rabbits fed the diet containing 1000mg/kg of Kemzyme had the highest (P<0.05) weight gain. Rabbits fed diets containing 250 and 500mg/kg of Kemzyme had the highest (P<0.05) feed conversion efficiency than those rabbits fed diets containing 1000mg/kg of Kemzyme. The control group had the lowest (P<0.05) feed conversion efficiency. Rabbits fed diets containing 1000mg/kg of Kemzyme had a significantly higher dress weight than those rabbits fed diets containing 250 and 500mg/kg of Kemzyme which were comparable but higher (P<0.05) than those of the control group. All those rabbits fed diets containing the Kemzyme had significantly higher carcass dressing than those of the control group, but those rabbits fed diets containing 250mg/kg of Kemzyme had similar (P>0.05) carcass dressing with the control. There was significant difference (P<0.05) among the treatment groups in terms of lung weight. In both the kidney and the liver, those rabbits fed the control diet had the highest kidney and liver weights and those rabbits fed diets containing 250mg/kg of Kemzyme had the lowest (P<0.05) weights. All those rabbits fed diets containing Kemzyme had superior (P<0.05) quality of blood in terms red blood cells, packed cell volume and haemoglobin than those rabbits fed the control diet. However, mean corpuscular volume was high (P<0.05) in the control group than those fed diets containing Kemzyme. Mean corpuscular haemoglobin concentration and white blood cells were not affected (P>0.05) by the inclusion of Kemzyme in the diets of the rabbits. In conclusion, supplementing diets with multi-enzyme (Kemzyme Dry-Plus) in increasing levels of 250mg/kg, 500mg/kg, and 1000mg/kg improved the growth performance of the weaner rabbits.